Fetal “Aortic coarctation” and different neonatal follow-up in 3 cases - Swięchowicz, Barbara; Respondek-Liberska, Maria (Prenatal Cardiology, 2017)
Heart defects which includes narrowing of aortic isthmus - aortic coarctation (CoA) are one of the most prevalent birth defects. Making a correct prenatal diagnosis of CoA is very difficult and problematic. We are still observing many false (+) and false (-) diagnoses. In presenting 3 cases with prenatal suspicion of CoA only one patient confirmed this defect in the postnatal life. In the fetal echocardiography inappropriate dimensions of great vessels and PA/Ao ratio are very relevant in the CoA diagnostics. Based on such suspicion before delivery we can select a group in which birth in the tertiary center, prostin infusion, control ECHO examinations and planned cardiac surgery will be needed. But wide differential diagnosis including pulmonary dilatation (due to pulmonary hypertension or fetal blood redistribution due to possible infection) is required.